2019
DOI: 10.1002/hep4.1419
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Related to Nonalcoholic Fatty Liver Disease Is Increasing in the United States

Abstract: Population‐level nonalcoholic fatty liver disease (NAFLD) death rate data are sparse. We described death rates for adults with NAFLD in the United States using mortality data from the National Vital Statistics System multiple‐cause mortality data (2007‐2016). Decedents who had NAFLD were identified by International Classification of Diseases (ICD) codes K75.81, K76.0, K74.0, K74.6, and K76.9. Among NAFLD decedents, cause‐specific deaths (e.g., cardiovascular disease [CVD], cirrhosis, hepatocellular carcinoma [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
127
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 179 publications
(150 citation statements)
references
References 42 publications
(51 reference statements)
3
127
0
2
Order By: Relevance
“…The prevalence of NAFLD currently is estimated to be approximately 30% in the general US population, and NAFLD, particularly in its most severe form, nonalcoholic steatohepatitis, has become an important risk factor for HCC in many countries, including the United States . However, individuals with NAFLD are more likely to die of cirrhosis, cardiovascular disease, diabetes, and non‐HCC cancer than they are to die of HCC . This suggests that the rising prevalence of NAFLD potentially could decrease the incidence of HCC.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of NAFLD currently is estimated to be approximately 30% in the general US population, and NAFLD, particularly in its most severe form, nonalcoholic steatohepatitis, has become an important risk factor for HCC in many countries, including the United States . However, individuals with NAFLD are more likely to die of cirrhosis, cardiovascular disease, diabetes, and non‐HCC cancer than they are to die of HCC . This suggests that the rising prevalence of NAFLD potentially could decrease the incidence of HCC.…”
Section: Introductionmentioning
confidence: 99%
“…NAFLD is a complex disease whose pathogenesis is dependent on an underlying genetic predisposition and several environmental factors. Recent data suggest that the global prevalence of NAFLD is rising as a consequence of the pandemic of obesity, insulin resistance and diabetes mellitus, which are common risk factors for both NAFLD and cardiovascular disease (CVD) . Although patients with NAFLD, specifically those with non‐alcoholic steatohepatitis (NASH), are at an increased risk for liver‐related mortality, evidence suggests that CV risk factors are major drivers of morbidity and mortality among patients with NAFLD …”
Section: Introductionmentioning
confidence: 99%
“…2,[9][10][11] Recent data suggest that the global prevalence of NAFLD is rising as a consequence of the pandemic of obesity, insulin resistance and diabetes mellitus, which are common risk factors for both NAFLD and cardiovascular disease (CVD). 3,[12][13][14] Although patients with NAFLD, specifically those with non-alcoholic steatohepatitis (NASH), are at an increased risk for liver-related mortality, evidence suggests that CV risk factors are major drivers of morbidity and mortality among patients with NAFLD. 10,[15][16][17][18][19] Recently, national efforts for CVD prevention via control of behavioural and biological risk factors have been undertaken.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that Mexican American ethnicity is associated with a higher risk for NAFLD but not necessarily a higher risk of advanced hepatic fibrosis and cirrhosis. (40)(41)(42) However, a recent study (43) showed increasing rates of NAFLD-related deaths among Mexican Hispanics and Asian Indians. Future studies are needed to clarify possible underlying genetic and environmental factors to explain these findings, and further study of the current data set is ongoing to investigate liver-related versus non-liver-related causes of death.…”
Section: Discussionmentioning
confidence: 99%